EFFECT OF TEMPERATURE AND TIME ON FLOW CHARACTERISTICS OF PANEER WHEY* - Sahu, Pranita; Agrawal, Ashok Kumar; Sahu, Chandrahas; Sahu, Ruchi (Indian Journal of Dairy Science, 2014)
Whey is the fluid by-product obtained during the manufacture of products like paneer, cheese and casein. Beside water whey contains lactose, protein, fat and ash. Whey can be converted into various types of product, viz, whey powder, lactose, high protein whey powder, demineralized whey powder, whey protein concentrate powder etc. For converting whey into these products, processing is necessary, which invariably depends on flow characteristics. Therefore, the objective of the present investigation was to determine the effect of temperature and time on friction and viscous properties of paneer whey. These properties were determined considering 3 levels of temperature (20, 25 and 30oC) and 3 time intervals (1, 2 and 3 h). ‘Reynold’s apparatus’ set up separately and ‘Pipe friction apparatus’ mounted on hydraulic bench (with a sump and a measuring tank) were used in present experimentation. The effect of temperature and time on Reynold’s number and head loss due to friction were determined for flow of whey in a particular diameter pipe with a particular velocity. There was not much appreciable effect on viscous characteristics with respect to temperature, whereas the time elapsed had shown significant effect on Reynolds number and head loss due to friction. Similarly, there was not much appreciable effect on variation of absolute viscosity with respect to time, whereas the temperature had shown significant effect. The data generated in the present investigation can be utilized as guidelines for designing of whey based processing systems.